The Impact of Motivation and Work Stress on Employee Performance at the Secretariat of the Regional People's Representative Council of Karawang Regency - Prasetyo, Tri; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to determine the partial and simultaneous effects of work motivation and work stress on the performance of employees of the Secretariat of the Regional People's Representative Council (DPRD) of Karawang Regency. The method used in this research is descriptive verification method. This research was conducted at the Karawang Regency DPRD Secretariat. The sample of this study amounted to 90 employees of the Karawang Regency DPRD Secretariat The sampling technique in the study used the saturated sampling method. The analysis model used in this research is multiple linear regression analysis model. The results showed that there was a partial effect of work motivation and work stress on the performance of employees of the Karawang Regency DPRD Secretariat. Simultaneously, the magnitude of the influence of work motivation and work stress on employee performance is 35.6%, while the remaining 64.4% is explained by other factors not examined in this study.